Single-mode surface-emitting concentric-circular-grating terahertz quantum cascade lasers - Liang, Guozhen (2013)
We demonstrate single-mode surface-emitting terahertz frequency quantum cascade lasers utilising non-uniform second-order distributed feedback concentric-circular-gratings. The grating is designed for single-mode operation and surface emission for efficient and directional optical power out-coupling. The devices exhibit single-mode operation over the entire dynamic range with a sidemode- suppression-ratio of around 30 dB at 78 K, and a six-fold rotationally symmetric far-field pattern. In addition, the devices show a peak output power approximately three times higher than in ridge-waveguide lasers of similar size, whilst maintaining similar threshold current densities for the 3.8 THz emission and without remarkably sacrificing the maximum temperature operation performance. Owing to the high symmetry of the structure and the broad area light emission from surface, the devices are potentially very suitable for use as single-mode, high power emitters for integration into two-dimensional laser arrays.